Implications of Open Source Blockchain for increasing efficiency and transparency of the Digital Content Supply Chain in the Australian Telecommunications and Media Industry - Plant, Laurence (Journal of Telecommunications and the Digital Economy, 2017)
While digital content is key to the Australian Telecommunications and Media industry, there is little industry cooperation to improve the content lifecycle across industry segments including production, distribution and advertising. With the emergence of hyperledger, an open source blockchain technology for shared ledger, there is opportunity for the industry to collaborate to improve content lifecycle transparency, trust and efficiency while protecting consumer privacy. Individual business networks and supply chains within the industry can tactically deploy hyperledger as a shadow ledger as a starting point, and widespread, consistent industry adoption is more readily achieved through government regulatory guidelines and a wholesale digital content infrastructure provider taking a leading role.